Simultaneous analysis of 210 prohibited substances in human urine by ultrafast liquid chromatography/tandem mass spectrometry in doping control. (9th January 2015) - Jeong, Eun Sook; Kim, So‐Hee; Cha, Eun‐Ju; Lee, Kang Mi; Kim, Ho Jun; Lee, Sang‐Won; Kwon, Oh‐Seung; Lee, Jaeick
Abstract : RATIONALE: Doping analysis is a two‐step process consisting of a screening step for prohibited substances and a confirmation step to verify the presence of specific substances found during the screening. The entire process must be performed within a limited time period, but traditional screening procedures commonly employ separate analytical methods for each class of prohibited substances being screened and thus require a great deal of human resources and instrumentation. A single simple and rapid multiresidue analytical method that could accommodate multiple classes of prohibited substances would be extraordinarily useful in doping analyses. METHODS: Urine samples were extracted via two consecutive liquid–liquid extractions at different pH values following enzymatic hydrolysis. Analyses were performed by ultrafast liquid chromatography/triple‐quadrupole mass spectrometry with polarity switching and time‐dependent selected reaction monitoring. RESULTS: We developed a rapid multiresidue screening and confirmation method for efficient high‐throughput doping analyses. The present method was validated with regard to the limits of detection (0.01–100.0 ng/mL for screening analyses and 0.2–500.0 ng/mL for confirmation assays), matrix effects (48.9–118.9%), recovery (20.6–119.7%) and intra‐ (0.6–17.6%) and inter‐day (4.0–20.0%) precision. CONCLUSIONS: A multiresidue analytical method was developed and validated for screening and confirming the presence of performance‐enhancing drugs. A total of 210 substances from diverse classes of prohibited substances were successfully identified with an analytical run time of 10 min. Copyright © 2015 John Wiley & Sons, Ltd.